Desain Model Database Mutasi Siswa Dengan Menerapkan Metode Database Life Cycle - Samidi, Samidi; Hidayat, Ramdhani (Technomedia Journal, 2023)
Students in a number of conditions and reasons can apply for transfers in and out or transfer from school of origin to school of destination. Mutations of students cause data changes, so that for the efficiency of data adjustment it is necessary to implement the database life cycle method. This study aims to design a student mutation database model design by applying the database life cycle method. This study uses a case study research method with data collection methods through library research, namely exploring journals, books and other information relevant to the study. The database model analysis and design uses the Database Life Cycle (DBLC) method which focuses on conceptual database design, logical database design, and physical database design. The result of this design is a database design model by applying the DBLC method which has relationships between tables or relational and has the main function of storing and maintaining data and being able to answer information management needs which are expected to facilitate the student transfer process.